The Relationship Between Emotion Regulation and Cyberbullying Behavior Among Students at SMKN 1 Kaidipang - Riska Riska; Anik Indarwati; Sri Ayu Mutmainah Kurniawati (Utan Kayu Publishing, 2025)
This study aims to examine the relationship between emotion regulation and cyberbullying behavior among students at SMK Negeri 1 Kaidipang. Cyberbullying is a form of digital aggression that is prevalent among adolescents and is often triggered by negative emotions and poor emotional management skills. The research adopts a quantitative approach using a correlational survey method. The sample consisted of 37 students selected through purposive sampling. The research instruments included an emotion regulation scale based on Gross's theory and a cyberbullying behavior scale referring to aspects identified by Hinduja and Patchin. Data analysis using Pearson correlation revealed a significant negative relationship between emotion regulation and cyberbullying behavior (r = -0.483; p = 0.002). This indicates that the better students regulate their emotions, the lower their tendency to engage in cyberbullying.